Highlighting allelic variations at the interleukin-19 locus in term of preeclampsia predisposing factors and access to an accurate diagnostic/screening option - Sara Parhoudeh; Aida Saadaty; Khalil Khashei Varnamkhasti; Samire Khashei Varnamkhasti; Leila Naeimi; Sirous Naeimi (BMC, 2023)
Abstract Background Preeclampsia is the main cause of preterm parturition and maternal-fetal complications. T helper 1 and T helper 2 cytokines balance is a requirement in normal pregnancy and aberrant in this immunologic balance, play an important role in the pathology of preeclampsia. In previous studies single nucleotide polymorphisms have been associated with the alteration of serum cytokine levels. Objective This study was aimed to discover association between interleukin-13 (rs20541, and rs56035208) and interleukin-19 (rs1028181 (T/C) and rs2243191(T/C)) polymorphisms with susceptibility to preeclampsia. Methods In this case-control study 300 women with and without preeclampsia (n = 150/each) who referred to Zeynabieh Hospital- Shiraz, Iran, from February 2021 to April 2022 were enrolled. For genotyping the interleukin-13 and interleukin-19 polymorphisms, the Allele-specific polymerase chain reaction and direct sequencing method was carried out. Results Our statistical results revealed no significant differences in allele and genotype frequencies for interleukin-13 polymorphisms compared to controls. We found that the interleukin‐13 polymorphisms are significantly associated with vulnerability to edema at rs20541 position and maternal drinking at rs56035208 position. But it was interesting to note that the differences of both the allele and genotype frequencies of interleukin-19 polymorphisms and their contribution to the risk of preeclampsia susceptibility were significant. Conclusions No risk of preeclampsia was found in all comparisons for interleukin-13 polymorphisms. However, the interleukin-19 polymorphisms were found to confer the risk of preeclampsia in our population.